Estimation of radiation doses and lifetime attributable risk of radiation-induced cancer in the uterus and prostate from abdomen pelvis CT examinations - Shubayr, Nasser; Alashban, Yazeed (Frontiers in Public Health, 2023)
Computed tomography (CT) scans are one of the most common radiation imaging modalities, and CT scans are rising steadily worldwide. CT has the potential to enhance radiography practice, but it also has the risk of drastically increasing patient doses. One CT procedure for the abdomen pelvis (AP) area can expose a patient’s prostate or uterus to a substantial radiation dose, leading to concerns about radiation-induced cancer. This study aimed to estimate organ doses of the uterus and prostate and evaluate the lifetime attributable risk (LAR) of cancer incidence and mortality resulting from AP CT examinations. This retrospective study included 665 patients, of which 380 (57%) were female, and 285 (43%) were male. Data were collected from the picture archiving and communication system for AP CT procedures and exposure parameter data. Organ doses for the uterus and prostate were calculated using National Cancer Institute CT (NCICT) software. Based on the risk models proposed by the BEIR VII report, the calculated organ doses were used to estimate the LAR of prostate and uterus cancer incidence and mortality due to radiation exposure from AP CT procedures. The mean effective dose resulting from AP CT for females and males was 5.76 ± 3.22 mSv (range: 1.13–12.71 mSv) and 4.37 ± 1.66 mSv (range: 1.36–8.07 mSv), respectively. The mean organ dose to the uterus was 10.86 ± 6.09 mGy (range: 2.13–24.06 mGy). The mean organ dose to the prostate was 7.00 ± 2.66 mGy (range: 2.18–12.94 mGy). The LAR of uterus and prostate cancer incidence was 1.75 ± 1.19 cases and 2.24 ± 1.06 cases per 100,000 persons, respectively. The LAR of cancer mortality rates from uterus and prostate cancers were 0.36 ± 0.22 and 0.48 ± 0.18 cases per 100,000 persons, respectively. The LAR of prostate and uterus cancer occurrence and mortality from radiation doses with APCT procedures was low but not trivial. Therefore, efforts should be made to lower patient doses while retaining image quality. Although the minimisation of the patient's radiation dose must guide clinical practice, the estimated slight increase in risk could aid in easing fears regarding well-justified AP CT procedures.